Answer:
1/3
Step-by-step explanation:
360/120=3
<span>Surface Area =<span> (2 • <span>π <span>• r²) + (2 • <span>π • r • height)
</span></span></span></span></span>
<span>(2 • <span>π <span>• r²) is surface area of the "ends"
</span></span></span>
<span>(2 • <span>π <span>• r • height) is lateral area
</span></span></span>
<span>Lateral Area = 2 * PI * 2 * 7
</span>
<span>Lateral Area =28 * PI =
</span>
<span><span><span>87.9645943005 square inches</span></span></span><span><span><span>
</span>
</span>
</span>
Answer is B
Answer: 7 bundles.
Step-by-step explanation:
The cost per bundle is $75.
The cost for shipping is $42.50
She spent $567.50 in total.
The shipping is paid only one time, as all the bundles can be packaged togheter.
Then after paying the shipping, the left spent is:
$567.50 - $42.50 = $525
And each bundle costs $75, then the number of bundles that she bought will be equal to the number of times that we have $75 in $525. This is equal to the quotient between $525 and $75.
N = $525/$75 = 7
She bought 7 bundles
Answer:
-2
Step-by-step explanation:
Distribute
2
(
3
+
4
)
+
2
=
4
+
3
{\color{#c92786}{2(3x+4)}}+2=4+3x
2(3x+4)+2=4+3x
6
+
8
+
2
=
4
+
3
{\color{#c92786}{6x+8}}+2=4+3x
6x+8+2=4+3x
2
Add the numbers
6
+
8
+
2
=
4
+
3
6x+{\color{#c92786}{8}}+{\color{#c92786}{2}}=4+3x
6x+8+2=4+3x
6
+
1
0
=
4
+
3
6x+{\color{#c92786}{10}}=4+3x
6x+10=4+3x
3
Rearrange terms
6
+
1
0
=
4
+
3
6x+10={\color{#c92786}{4+3x}}
6x+10=4+3x
6
+
1
0
=
3
+
4
6x+10={\color{#c92786}{3x+4}}
6x+10=3x+4
4
Subtract
1
0
10
10
from both sides of the equation
6
+
1
0
=
3
+
4
6x+10=3x+4
6x+10=3x+4
6
+
1
0
−
1
0
=
3
+
4
−
1
0
6x+10{\color{#c92786}{-10}}=3x+4{\color{#c92786}{-10}}
6x+10−10=3x+4−10
5
Simplify
Subtract the numbers
Subtract the numbers
6
=
3
−
6
6x=3x-6
6x=3x−6
6
Subtract
3
3x
3x
from both sides of the equation
6
=
3
−
6
6x=3x-6
6x=3x−6
6
−
3
=
3
−
6
−
3
6x{\color{#c92786}{-3x}}=3x-6{\color{#c92786}{-3x}}
6x−3x=3x−6−3x
7
Simplify
Combine like terms
Combine like terms
3
=
−
6
3x=-6
3x=−6
8
Divide both sides of the equation by the same term
3
=
−
6
3x=-6
3x=−6
3
3
=
−
6
3
\frac{3x}{{\color{#c92786}{3}}}=\frac{-6}{{\color{#c92786}{3}}}
33x=3−6
9
Simplify
Cancel terms that are in both the numerator and denominator
Divide the numbers
=
−
2